PENGARUH ONLINE CUSTOMER REVIEW, HARGA DAN ONLINE CUSTOMER RATTING TERHADAP KEPUTUSAN PEMBELIAN MELALUI TOKOPEDIA (Studi Pada Konsumen Toko Online Ventela Store Official di Kota Medan) - Purba, Eko Arianto; Safrin, Feby Aulia (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
This study aims to analyze how the influence of online customer reviews, prices and online customer ratting on consumer purchasing decisions Ventela store in Medan city. The influence between online costumer reviews, prices and online costumer ratting will be analyzed partially and simultaneously on employee performance. The form of research used in this research is quantitative research with an associative approach. Sampling was done through non-probability sampling techniques and used 100 respondents as samples. The research findings show that: The results of this study indicate that Online customer review and Online customer review have a significant effect, both partially and simultaneously (together) on consumer purchasing decisions. However, price has no significant effect on consumer purchasing decisions. Thus, the results of this study make an important contribution to the management of Ventela stores in Medan city in improving marketing strategies and employee performance management. Ventela store management can utilize online customer reviews and ratings as one of the factors that can improve consumer purchasing decisions and employee performance.